Undergraduate nurses' experience of the family health assessment as a learning opportunity - Juliana J. Willemse; Elma W. Kortenbout (AOSIS, 2012)
The practice of community health nursing (CHN) may enhance the life experiences of families and communities, particularly amongst the poor and socially marginalised. CHN provides for a deeper understanding of the health status of families living within communities, for example, where and how they live, their cultural context and their ability to identify resources available to assist with their health care (Allender, Rector & Warner 2010:17).This qualitative phenomenological study reflects on the self-reported lived experiences of undergraduate CHN students at the University of the Western Cape in the City of Cape Town, South Africa. These students conducted a family health assessment (FHA) learning task at the homes of families within communities.Purposive and convenience sampling was used by students who had conducted an FHA. Fourteen students agreed to participate in the study, of whom nine were interviewed, two withdrew and the remaining three were not interviewed since no new data were emerging during interviews, indicating that saturation had been reached. During in-depth interviews with seven female and two male students, data for the exploration of the lived experiences was gathered through the following question: 'How did you experience the FHA?' Field notes were taken and used to capture non-verbal communication of participants. The focus of the study was to explore the lived experiences of students and not those of the family on whom the FHA was completed.Data collected were categorised into themes, guided by the systematic data analysis process of Tesch (1990) cited in Cresswell (2003:192). Four themes emerged: challenges of family selection, challenges of safety, socio-cultural challenges and academic challenges experiencedby the participants. This study will inform future research and curriculum planning for CHN education in a multifaceted context.